Transtorno do déficit de atenção e hiperatividade: um estudo de rastreamento entre escolares de Castanhal/PA - NOBRE, João Paulo dos Santos (Universidade Federal do Pará, 2017)
The Attention Deficit Hyperactivity Disorder (ADHD) is an atypical condition of development, characterized by the triad of inattention, hyperactivity and impulsivity. A high incidence among children disorder worldwide, with an estimated prevalence of 5% to 7% in this population is considered, reaching predominantly. Although there is agreement when its high incidence, epidemiological studies worldwide do not find agreement on its impact. Nevertheless, it is possible to observe consensus among these studies, such as that ADHD involves losses in several areas of functioning, is more common in academic performance implications, the establishment of appropriate social relationships and family relationships. The treatment involves psychopedagogic attention psychotherapy and in some cases, use of medications. The aim of this study was to trace characteristic of ADHD among students of Castanhal municipal network in Pará, State of the Amazon region. The study gathered 39 elementary school teachers, comprising the 1st to 9th, three municipal schools responding to scale Scale Swanson, Nolan and Pelham - SNAP IV about the behavior of 279 randomly selected students enrolled and attended classes in the academic year 2015. In addition, data from the Basic Education Development Index were used (IDEB) of the school year 2015. The results of this study indicate prevalence of ADHD in 57 (20.43%) of which 41 (71.93%) were female and 16 (28.07%) were male. Regarding the presentation type, the most frequent was Inattention, 14 (24.56%) Combined type and 9 (15.79%) Hyperactivity. Obtained also a positive correlation between ADHD and School Delay from Total 57 participants with ADHD, 42 (73.61%) had school delay while the 222 considered without ADHD, 81 (36.49%). These data corroborate the literature pointing ADHD as a clinical condition with a negative impact in many areas of life of its own, one of the areas most affected academic life.